Imam Muhammad bin Husain Al-Jurri: Teacher Ethics in Educating Students - Napitupulu, Saripuddin; Aprison, Wedra; Ronaldo, Muhammad (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2025)
This study aims to examine the ethics of teachers in educating students based on the thoughts of Imam Muhammad bin Husain Al-Jurri. Through a qualitative approach, the researcher uses data obtained from library sources, such as books, articles, or journals and this study analyzes the works of Al-Jurri, especially the book Adab Thalabi al-'Ilmi, to explore ethical values ​​that are relevant to teaching. This study highlights the importance of sincere intentions, justice, and gentleness in educating as the main principles that must be applied by educators. In addition, Al-Jurri emphasizes the need to face the Qibla, be fair to students without distinguishing social status, and avoid rude attitudes when teaching. The findings of this study are relevant in facing the challenges of modern education, such as the moral crisis of the younger generation, by emphasizing the role of teachers as moral role models. The integration of ethical values ​​in teaching is expected to support the development of students' character and spirituality, creating education that is not only oriented towards academics but also on the formation of a complete personality. It is hoped that this research will provide new contributions to research on Islamic educational ethics.